PENGARUH PREMI ASURANSI DAN KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH PT. ASURANSI JIWA SEQUIS LIFE MEDAN - Irvan Rolyesh Situmorang; Wilys Hendrian (LPPM STIE EKA PRASETYA, 2019)
This research aims to analyze the influence of Insurance Premium and Service Quality on Customer Satisfaction at PT. Asuransi Jiwa Sequis Life Rising Star Agency Medan., to analyze the influence of Insurance Premium on Customer Satisfaction at PT. Asuransi Jiwa Sequis Life Rising Star Agency Medan., and to analyze the influence of Service Quality on Customer Satisfaction at PT. Asuransi Jiwa Sequis Life Rising Star Agency Medan The research methodology used quantitative descriptive method. Data type which was used in this study was quantitative data, which is obtained in number form. Data sources were primary and secondary data. Primary data was obtained from questionnaire distribution to who bought Q Smart Life insurance policy product at PT. Asuransi Jiwa Sequis Life Rising Star Agency Medan, and secondary data obtained from data and literature relating to this research. The population in this research was the people who bought Q Smart Life insurance policy product at PT. Asuransi Jiwa Sequis Life Rising Star Agency Medan, which numbered around 26.550 people. By using the Slovin formula, then totally of sample was 100 people. Data was analyzed by using multiple linear regression analysis method. Results of the analysis showed that Insurance Premium had a positive and significant influence on Customer Satisfaction based on partial. The results also showed that Service Quality had a positive and significant influence on Customer Satisfaction based on partial. And finally it showed that Insurance Premium and Service Quality had a positive and significant influence on Customer Satisfaction Interest based on simultaneously. This research hypothesis results was supported 62.9%, which meant that Insurance Premium and Service Quality simultaneously had 62.9% influence on Customer Satisfaction at PT. Asuransi Jiwa Sequis Life Rising Star Agency Medan. While the remaining about 37.1% was influenced by other variables which was not examined in this research example economic situation, brang image and marketing mix.